(untitled) (Medical Forum Monthly, 2023)
Objective: Abdominal trauma patients were the focus of this study in order to explore the factors that influence their recovery. Study Design: A retrospective cohort study Place and Duration of Study: This study was conducted at the Department of Surgery in LRH Peshawar from 15-Jan 2021 to 15-Jan 2022. Materials and Methods: To a trauma center due to abdominal trauma. Medical records were used to collect the patients' trauma scores, medical history, demographics, and outcomes. The scoring system consisted of the Injury Severity Score (ISS), the Revised Trauma Score (RTS), and the Abdominal Trauma Index (ATI). The outcomes were classified as favorable (discharge with full recovery) or unfavorable (death or disability). Results: An assessment determined the likelihood of patient success based on traits such as age, gender, and any comorbidities, as well as their trauma scores. Unfavorable outcomes were more probable for patients over 55 years old or those with comorbidities. The RTS, ISS, and ATI scores had a significant correlation to the outcome, meaning that patients who had low scores had a higher chance of an unfavorable outcome. Conclusion: In predicting outcomes for those with abdominal trauma, patient characteristics and trauma scores may be helpful, as this study shows. It is necessary to further research the role these factors play in determining outcomes for this patient population.